Molybdenum alloy composite powder with micro-nano multi-scale configuration and preparation method of molybdenum alloy
By adding layered Ti3Al and TiC ceramic materials to the molybdenum powder, a micro-nano multi-scale configuration molybdenum alloy composite powder was formed, and the problem of insufficient recrystallization temperature at high temperatures was solved through vacuum hot pressing sintering process. , significantly improves the compressive strength and high temperature performance of molybdenum alloy.
Patent Information
- Application Number
- CN202411698529.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-14
AI Technical Summary
The existing molybdenum alloy has insufficient recrystallization temperature at high temperatures and its strength decreases, making it difficult to meet the needs of ultra-high temperature equipment.
By adding layered Ti3Al and TiC ceramic materials to the molybdenum dioxide powder, hydrogen reduction treatment was performed to form a molybdenum alloy composite powder with a micro-nano multi-scale configuration, and a molybdenum alloy sintering blank was prepared by vacuum hot pressing sintering process.
It significantly improves the recrystallization temperature and compressive strength of molybdenum alloy at ultra-high temperatures, improves the high-temperature performance of molybdenum alloy, and meets the use needs of ultra-high temperature extreme environments.
Smart Images

Figure CN119433266A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of powder metallurgy, and in particular relates to a molybdenum alloy composite powder with micro-nano multi-scale configuration and a preparation method of the molybdenum alloy. Background Art
[0002] Molybdenum alloy is a key material for high-temperature structural components in nuclear fusion reactors and aerospace engineering. With the increasingly harsh service conditions of high-end equipment, higher requirements are placed on the recrystallization temperature, high-temperature stability and high-temperature mechanical properties of molybdenum alloys. It is urgent to develop high-performance molybdenum alloys that can be used in ultra-high temperature (above 1500 ℃) extreme environments. Second phase strengthening is an important way to improve the high-temperature performance of molybdenum alloys. The structure, morphology and quantity of the second phase are key factors affecting the high-temperature performance of molybdenum alloys. At present, the recrystallization temperature of molybdenum alloys is difficult to exceed 1400 ℃, and the strength drops significantly after recrystallization, which is difficult to meet the needs of high-temperature equipment. What kind of second phase to use and how to strengthen it to further significantly improve the high-temperature performance of molybdenum alloys is a key issue in this field.
[0003] The lamellar Ti3Al phase has good self-lubricity, a thermal expansion coefficient between ceramics and metals, and a high degree of compatibility with molybdenum alloys, making it one of the ideal choices for the new generation of molybdenum alloy reinforcement phases. Therefore, adding lamellar Ti3Al phases to disperse reinforced molybdenum alloys is expected to improve the strength of molybdenum alloys while improving their plasticity, thereby preparing molybdenum alloys with ultra-high recrystallization temperatures and room / high temperature toughness for use in extremely harsh environments.
[0004] Interfaces including grain boundaries (GBs) and phase boundaries (PBs) play a vital role in the comprehensive properties of polycrystalline materials. However, the segregation of some interstitial impurities such as oxygen (O) and nitrogen (N) at the grain boundaries is considered to be the main cause of the grain boundary brittleness and low plasticity of Mo alloys. Therefore, reducing impurities (such as oxygen, nitrogen, etc.) at the grain boundaries can effectively improve the strength and plasticity of molybdenum and its alloys. A large number of scholars have found that the addition of carbides can effectively inhibit the segregation of O at GBs, the interstitial oxygen at the grain boundaries reduces the cohesion of the grain boundaries, and C and TiC increase the fracture strength of the grain boundaries due to their strong Mo-C bonds, so that molybdenum and its alloys have excellent mechanical properties and thermal stability. Summary of the invention
[0005] The purpose of the present invention is to provide a molybdenum alloy composite powder with a micro-nano multi-scale configuration and a method for preparing a molybdenum alloy, so as to increase the recrystallization temperature of the molybdenum alloy, enhance the compressive strength of the molybdenum alloy at ultra-high temperatures, and meet the performance requirements of ultra-high temperature (above 1500°C) extreme environments.
[0006] The present invention is specifically implemented by the following technical scheme. According to the method for preparing a molybdenum alloy composite powder with a micro-nano multi-scale configuration and a molybdenum alloy proposed by the present invention, it comprises the following steps: (1) According to the requirements of the final product, MoO2 powder, Ti3Al ceramic material and TiC ceramic material are weighed in a certain mass ratio, mixed and ground using a vertical sand mill, and then spray-dried to obtain a precursor composite powder; In this step, the mass ratio of MoO2, Ti3Al, and TiC is (125~135): (0.5~2.5): (0.5~2.5); (2) The precursor composite powder obtained in step (1) is subjected to high-temperature reduction in a reducing atmosphere, wherein the reduction temperature is 700-850°C and the reducing atmosphere flow rate is 18-25 m 3 / h, reduction time 6-8 h, powder spreading height ≤1 / 2, to obtain molybdenum alloy composite powder with micro-nano multi-scale configuration; (3) According to the required size of the final product, a suitable rubber mold is selected, a certain amount of the molybdenum alloy composite powder prepared in step (2) is weighed and loaded into the rubber mold, a cold isostatic press is used for pressing, and then vacuum hot pressing and sintering are performed. After cooling in the furnace, a molybdenum alloy sintered blank with a micro-nano multi-scale structure is obtained.
[0007] Preferably, in step (1), the Ti3Al ceramic material used is in the form of lamellar sheets, with a purity of not less than 99% and a particle size of 2 to 8 µm; the TiC ceramic material has a purity of not less than 99% and a particle size of 3 to 5 µm; the MoO2 powder used has a particle size of 5 to 10 µm, and the content of impurity W is less than 50 ppm.
[0008] Preferably, the vertical sand mill used is a double-cylinder circulation, the grinding balls used are tungsten alloy balls, the ball-to-material ratio is 10:1, the particle size is 0.5-1 mm, the grinding medium is water, the vertical sand mill runs at a linear speed of 12-15 m / s, and the grinding time is 24-36 h; the mixed and ground slurry is transported to a spray dryer at a speed of 20-50 mL / min for spray drying, and the drying temperature is 250-300 ° C to prepare D 50 Precursor composite powders smaller than 500 nm.
[0009] Preferably, in step (2), the reducing atmosphere includes but is not limited to hydrogen.
[0010] Preferably, in step (3), the pressure of the cold isostatic pressing green sheet is 120-180 MPa, and the holding time is 10-20 min; the temperature of the vacuum hot pressing sintering is 1700-2100°C, the holding time is 6-10 h, the heating rate is 6-8°C / min, and the vacuum degree is less than 10 -3 MPa.
[0011] Prepared according to the aforementioned method, the molybdenum alloy composite powder obtained in step (2) includes molybdenum particles with a particle size of 10-15 nm and molybdenum particles with a particle size of 200-300 nm, the molybdenum particles of 10-15 nm are distributed between the micron-sized layered Ti3Al sheets, and the molybdenum particles of 200-300 nm are distributed in a nearly spherical shape around the micron-sized layered Ti3Al, forming a molybdenum alloy composite powder with a micro-nano multi-scale configuration.
[0012] The compressive strength of the molybdenum alloy sintered billet with micro-nano multi-scale structure prepared according to the above method is above 211 MPa at a high temperature of 1600 °C, which is more than 68.8% higher than that of pure molybdenum.
[0013] The present invention also provides a molybdenum alloy composite powder with micro-nano multi-scale configuration and a molybdenum alloy sintered blank prepared according to the above method.
[0014] Compared with the prior art, the present invention has obvious advantages and beneficial effects. By means of the above technical solution, the present invention can achieve considerable technical progress and practicality, and has a wide range of utilization value, and has at least the following advantages: (1) The present invention provides a molybdenum alloy composite powder with a micro-nano multi-scale configuration and a method for preparing a molybdenum alloy. Ti3Al and TiC ceramic materials are added to raw molybdenum dioxide powder, mixed and hydrogen-reduced to form a molybdenum alloy composite powder. The lamellar Ti3Al provides nucleation points and provides a confined growth space for molybdenum particles, thereby obtaining nano-scale molybdenum particles. In the molybdenum alloy composite powder, 10-15 nm molybdenum particles are distributed between the micron-scale lamellar Ti3Al sheets, and 200-300 nm molybdenum particles are distributed in a nearly spherical shape around the micron-scale lamellar Ti3Al, forming a molybdenum alloy composite powder with a micro-nano multi-scale configuration. In the subsequent vacuum hot pressing sintering process, the fine-grained nano-scale molybdenum powder is preferentially melted, which promotes sintering densification and improves the interface bonding relationship between the secondary phase and the molybdenum matrix, so that the density of the molybdenum alloy reaches more than 99%, and the average grain size is 3-10 μm. Micron-sized layered Ti3Al phases are distributed at the grain boundaries, and TiC reacts with oxygen impurities in the molybdenum matrix to form titanium oxide, which purifies the grain boundaries. Under long-term high-temperature sintering, titanium oxide is deoxidized to form nano-sized spherical sub-titanium oxide (Ti n O 2n-1 ) are dispersed inside the grains, accurately constructing a secondary phase-reinforced molybdenum alloy with micro-nano multi-scale configuration.
[0015] (2) The present invention adopts a vertical sand mill to grind and mix the powder, and the prepared composite powder is finer. The second phase particles are more evenly mixed with molybdenum dioxide under the action of the water medium. Compared with the traditional solid-solid doping, the precursor composite powder prepared by the present invention has higher surface quality and more uniform particle size, which improves the problem of particle entanglement and poor particle size uniformity in the traditional mechanical mixing method.
[0016] (3) The preparation process of the present invention introduces a secondary phase into the molybdenum alloy. The secondary phase not only provides nucleation points during the powder reduction process, effectively reducing the powder particle size, but also the unique lamellar structure of the secondary phase provides a confined growth space for the molybdenum particles, allowing the molybdenum particles to be further refined to the nanometer level. Nanoscale molybdenum particles preferentially melt during high-temperature sintering, promote sintering densification, and improve the interface bonding relationship between the secondary phase and the matrix. The structural organization of the obtained molybdenum alloy is more uniform, the recrystallization temperature of the molybdenum alloy is increased, and the strength of the molybdenum alloy at ultra-high temperatures is significantly improved. The compressive strength of the obtained molybdenum alloy sintered blank with a micro-nano multi-scale configuration is 285 MPa at 1600°C, which is 128% higher than the compressive strength of pure molybdenum without adding a secondary phase, thereby improving the performance of the molybdenum alloy in high-temperature scenarios and expanding the application range of the molybdenum alloy. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 (a) and (b) are SEM images of the molybdenum alloy composite powders with micro-nano multi-scale configurations prepared in Example 1 and Example 2, respectively. Figure 1 (c) is Figure 1 The EDS scan image in (b) is Figure 1 (d1)~(d4) Figure 1 EDS element distribution map in (c); Figure 2 (a), (b), and (c) are SEM images of the fracture surface of the molybdenum alloy sintered blank with micro-nano multi-scale structure prepared in Example 1 at different magnifications. Figure 2 (d)~(h) Figure 2 EDS element distribution diagram in (b); Figure 3 It is the compressive stress-strain curve of the molybdenum alloy sintered blank with micro-nano multi-scale configuration prepared in Examples 1 to 3 and the pure molybdenum prepared in the comparative example at a high temperature of 1600°C. DETAILED DESCRIPTION
[0019] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] The present invention is described in detail with specific examples below. If no specific conditions are specified in the following examples, they are all carried out according to conventional conditions or conditions recommended by the manufacturer. The raw materials and reagents used without specifying the manufacturer are all conventional products that can be purchased from the market.
[0021] Example 1 (1) According to the requirements of the final product, weigh 13.2 kg MoO2 and 50 g Ti3Al and 50 g TiC ceramic materials. The Ti3Al ceramic material used is in lamellar form with a purity of not less than 99% and a particle size of 2 to 8 µm. The purity of the TiC ceramic material is not less than 99% and a particle size of 3 to 5 µm. The particle size of the MoO2 used is 5 to 10 µm, and the content of impurity W is less than 50 ppm. MoO2, Ti3Al and TiC materials were mixed in a vertical sand mill. The vertical sand mill was a double-cylinder circulation mill. The grinding balls used were tungsten alloy balls with a ball-to-material ratio of 10:1 and a particle size of 0.5-1 mm. Water was used as the grinding medium. The linear speed of the sand mill was 12 m / s and the grinding time was 24 h. The mixed and ground slurry was transported to a spray dryer at a speed of 50 mL / min for spray drying at a drying temperature of 300 °C to obtain D 50 Precursor composite powders smaller than 500 nm; (2) The precursor composite powder is reduced at high temperature in a hydrogen atmosphere at a reduction temperature of 700°C and a hydrogen flow rate of 18 m 3 / h, reduction time 6 h, powder spreading height ≤ 1 / 2, to obtain molybdenum alloy composite powder with micro-nano multi-scale configuration; (3) The prepared molybdenum alloy composite powder with micro-nano multi-scale structure was pressed in a 180 MPa cold isostatic press for 15 min, and then vacuum hot-pressed sintered at a sintering temperature of 1700 °C, a holding time of 8 h, a heating rate of 6 °C / min, and a vacuum degree of <10 -3 MPa, and after cooling in the furnace, a molybdenum alloy sintered blank with micro-nano multi-scale structure was obtained. According to the test, the compressive strength of the molybdenum alloy sintered blank at 1600℃ is 285 MPa.
[0022] Example 2 The difference from Example 1 is: (1) The masses of MoO2, Ti3Al, and TiC were 13 kg, 100 g, and 100 g, respectively. The sand mill was operated at a linear speed of 15 m / s and the grinding time was 30 h. The mixed and ground slurry was transported to a spray dryer at a speed of 30 mL / min for spray drying at a drying temperature of 250 °C to obtain D 50 Precursor composite powders smaller than 500 nm; (2) Reduction temperature is 750°C and hydrogen flow rate is 20 m 3 / h, reduction time 8 h, powder spreading height ≤ 1 / 2, to obtain molybdenum alloy composite powder with micro-nano multi-scale configuration; (3) The prepared molybdenum alloy composite powder with micro-nano multi-scale structure was pressed in a 150 MPa cold isostatic press for 20 min, and then vacuum hot-pressed sintered at a sintering temperature of 1900 °C, a holding time of 7 h, a heating rate of 8 °C / min, and a vacuum degree of <10 -3 MPa, and after cooling in the furnace, a molybdenum alloy sintered blank with micro-nano multi-scale structure was obtained. According to the test, the compressive strength of the molybdenum alloy sintered blank at 1600℃ is 272 MPa.
[0023] Example 3 The difference from Example 1 is: (1) The masses of MoO2, Ti3Al, and TiC were 12.5 kg, 200 g, and 200 g, respectively. The sand mill was operated at a linear speed of 15 m / s and the grinding time was 36 h. The mixed and ground slurry was transported to a spray dryer at a speed of 50 mL / min for spray drying at a drying temperature of 280 °C to obtain D 50 Precursor composite powders smaller than 500 nm; (2) Reduction temperature is 800°C and hydrogen flow rate is 18 m 3 / h, reduction time 6 h, powder spreading height ≤ 1 / 2, to obtain molybdenum alloy composite powder with micro-nano multi-scale configuration; (3) The prepared molybdenum alloy composite powder with micro-nano multi-scale structure was pressed in a 190 MPa cold isostatic press for 15 min, and then vacuum hot-pressed sintered at a sintering temperature of 2100 °C, a holding time of 6 h, a heating rate of 8 °C / min, and a vacuum degree of <10 -3 MPa, and after cooling in the furnace, a molybdenum alloy sintered blank with micro-nano multi-scale structure was obtained. According to the test, the compressive strength of the molybdenum alloy sintered blank at 1600℃ is 211 MPa.
[0024] Comparative Example 1 (1) According to the requirements of the final product, a certain amount of MoO2 was weighed, the particle size of the molybdenum dioxide used was 5-10 µm, and the content of impurity W was less than 50 ppm; a vertical sand mill was used for ball milling, the vertical sand mill was a double-cylinder circulation, the grinding balls used were tungsten alloy balls, the ball-to-material ratio was 10:1, the particle size was 0.5-1 mm, water was used as the grinding medium, the sand mill was operated at a linear speed of 12 m / s, and the grinding time was 20 h; the mixed and ground slurry was transported to a spray dryer at a speed of 50 mL / min for drying, and the drying temperature was 250 °C to prepare D 50 Powders smaller than 500 nm; (2) The powder prepared in step (1) is reduced at high temperature in a reducing gas hydrogen atmosphere, with the reduction temperature being 700°C and the hydrogen flow rate being 18 m 3 / h, reduction time 6 h, to obtain molybdenum powder; (3) The prepared molybdenum powder was pressed in a 180 MPa cold isostatic press for 15 min, and then vacuum hot-pressed sintered at a sintering temperature of 1700 °C, a holding time of 8 h, a heating rate of 6 °C / min, and a vacuum degree of <10 -3 MPa, and pure molybdenum is obtained after cooling in the furnace. According to the test, the compressive strength of pure molybdenum at 1600℃ is 125 MPa.
[0025] Figure 1 is a SEM image of the molybdenum alloy composite powder with micro-nano multi-scale configuration prepared in step (2) of Examples 1-2, Figure 1 In (a) and (b), respectively, it can be seen that the layered secondary phase provides a confined growth space for the nucleation molybdenum particles, and the prepared molybdenum particles are further refined to the nanometer level. The molybdenum particles with a smaller particle size of 10-15 nm are distributed between the sheets of the micron-sized layered Ti3Al phase, and the molybdenum particles of 200-300 nm are distributed in a nearly spherical shape around the micron-sized layered Ti3Al, forming a molybdenum alloy composite powder with a micro-nano multi-scale configuration. Figure 1 (c) is Figure 1 The EDS scan image in (b) is Figure 1 (d1)~(d4) Figure 1 EDS element distribution diagram in (c); it can be seen that the smaller molybdenum particles are distributed inside and on the surface of the micron-sized layered Ti3Al, and the larger molybdenum particles are distributed around the micron-sized layered Ti3Al. At the same time, there is a small amount of impurity oxygen in the molybdenum powder.
[0026] Figure 2 (a), (b), and (c) are SEM images of the fracture surface of the molybdenum alloy sintered blank with micro-nano multi-scale structure prepared in step (3) of Example 1 at different magnifications. It can be seen that the spherical titanium oxide (Ti n O 2n-1) are dispersed inside the molybdenum grains, and the layered secondary phase is distributed at the grain boundaries, accurately constructing a multi-scale secondary phase-reinforced molybdenum alloy with a micro-nano hybrid configuration. Figure 2 (d)~(h) Figure 2 From the EDS element distribution diagram in (b), it can be seen that the layered secondary phase Ti3Al exists at the grain boundaries.
[0027] Figure 3 It is the compressive stress-strain curve of the molybdenum alloy sintered billet with micro-nano multi-scale structure prepared in Examples 1 to 3 and the pure molybdenum prepared in the comparative example at a high temperature of 1600°C. It can be seen that the compressive strength of the molybdenum alloy sintered billet with micro-nano multi-scale structure prepared in Examples 1 to 3 is significantly improved compared with that of pure molybdenum, and the compressive strength of the molybdenum alloy sintered billet with micro-nano multi-scale structure prepared in Example 1 is increased by 128% compared with the pure molybdenum in the comparative example.
[0028] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. A method for preparing a molybdenum alloy composite powder with a micro-nano multi-scale configuration and a molybdenum alloy, characterized in that The following steps are involved: (1) According to the requirements of the final product, MoO2 powder, Ti3Al ceramic material and TiC ceramic material are weighed in a certain mass ratio, mixed and ground using a vertical sand mill, and then spray-dried to obtain a precursor composite powder; In this step, the mass ratio of MoO2, Ti3Al, and TiC is (125~135): (0.5~2.5): (0.5~2.5); (2) The precursor composite powder obtained in step (1) is reduced at high temperature in a reducing atmosphere, wherein the reduction temperature is 700-850°C and the reducing atmosphere flow rate is 18-25 m 3 / h, reduction time 6-8 h, powder spreading height ≤1 / 2, to obtain molybdenum alloy composite powder with micro-nano multi-scale configuration; (3) According to the required size of the final product, a suitable rubber mold is selected, a certain amount of the molybdenum alloy composite powder prepared in step (2) is weighed and loaded into the rubber mold, a cold isostatic press is used for pressing, and then vacuum hot pressing and sintering are performed. After cooling in the furnace, a molybdenum alloy sintered blank with a micro-nano multi-scale structure is obtained.
2. The method for preparing the molybdenum alloy composite powder and molybdenum alloy with micro-nano multi-scale configuration as claimed in claim 1, characterized in that In step (1), the Ti3Al ceramic material used is in the form of lamellar sheets, with a purity of not less than 99% and a particle size of 2 to 8 µm; the TiC ceramic material has a purity of not less than 99% and a particle size of 3 to 5 µm; the MoO2 powder used has a particle size of 5 to 10 µm, and the content of impurity W is less than 50 ppm.
3. The method for preparing the molybdenum alloy composite powder and molybdenum alloy with micro-nano multi-scale configuration as claimed in claim 1, characterized in that In step (1), the vertical sand mill used is a double-cylinder circulation, the grinding balls are tungsten alloy balls, the ball-to-material ratio is 10:1, the particle size is 0.5-1 mm, the grinding medium is water, the vertical sand mill runs at a linear speed of 12-15 m / s, and the grinding time is 24-36 h.
4. The method for preparing the molybdenum alloy composite powder and molybdenum alloy with micro-nano multi-scale configuration as claimed in claim 1, characterized in that In step (1), the mixed and ground slurry is transported to a spray dryer at a rate of 20-50 mL / min for spray drying at a drying temperature of 250-300 °C to obtain D 50 Precursor composite powders smaller than 500 nm.
5. The method for preparing the molybdenum alloy composite powder and molybdenum alloy with micro-nano multi-scale configuration as claimed in claim 1, characterized in that In step (3), the pressure of the cold isostatic pressing of the green sheet is 120 to 180 MPa, and the holding time is 10 to 20 min.
6. The method for preparing the molybdenum alloy composite powder and molybdenum alloy with micro-nano multi-scale configuration as claimed in claim 1, characterized in that In step (3), the vacuum hot pressing sintering temperature is 1700-2100°C, the holding time is 6-10 h, the heating rate is 6-8°C / min, and the vacuum degree is less than 10 -3 MPa.
7. The method for preparing the molybdenum alloy composite powder and the molybdenum alloy with micro-nano multi-scale configuration according to any one of claims 1 to 4, characterized in that The molybdenum alloy composite powder obtained in step (2) includes molybdenum particles with a particle size of 10-15 nm and molybdenum particles with a particle size of 200-300 nm, wherein the molybdenum particles with a particle size of 10-15 nm are distributed between the micron-sized layered Ti3Al sheets, and the molybdenum particles with a particle size of 200-300 nm are distributed in a nearly spherical shape around the micron-sized layered Ti3Al, forming a molybdenum alloy composite powder with a micro-nano multi-scale configuration.
8. The method for preparing the molybdenum alloy composite powder and the molybdenum alloy with micro-nano multi-scale configuration according to any one of claims 1 to 6, characterized in that The prepared molybdenum alloy sintered billet with micro-nano multi-scale structure has a compressive strength of over 211 MPa at 1600°C.
9. The molybdenum alloy composite powder with micro-nano multi-scale structure and the molybdenum alloy sintered blank obtained by the preparation method according to any one of claims 1 to 6.